STRATEGI DALAM MENINGKATKAN VOLUME PENJUALAN MOBIL DI KOTA MEDAN PADA MASA PANDEMI COVID-19 - Mhd Irwan Padli Nasution, Annio Indah Lestari, Nurul Badriah, (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2021)
The purpose of this study is to determine and analyze the car sales strategy carried out by Auto 2000 Medan Pancing. The research method used is a SWOT analysis and a qualitative descriptive analysis method. This method is a data analysis method that is not in the form of numbers but in the form of a series of information extracted from research results. The author must first know how the state of the company, its internal and external factors, what influences the existing marketing strategy of the company. The data collection technique carried out by the researcher is to conduct interviews and direct observations on the marketing manager. The data obtained from the data collection is then analyzed using SWOT analysis to find out what are the strengths, weaknesses, opportunities and threats of the marketing strategy carried out by the company. The SWOT results show that the company is in a strong condition and has a lot of opportunities.